Does the Zambian Legal Environment Support Informal Enterprises` Transition into the Formal Economy? (Global Journal of Management and Business Research, 2023)
Abstract- This article provides findings from a study which examined ways in which the Zambian legal environment supports informal enterprises transition into the formal economy This qualitative study adopted a phenomenological research design Data was collected via structured interviews from 11 respondents who were purposively selected Thematic and content analysis of the data were used to come up with the findings of the study The findings established that a few laws and policies support and facilitate transitioning from informal to the formal Zambian economy Further the findings indicated that enterprises were critical to the economy because of the contribution they made through employment creation and poverty reduction activities against the desired outcome by government to have a smaller informal economy in relation to the formal economy The study also established reasons why some informal enterprises are non-compliant to government compliance requirements Based on the finding of the study it was recommended that regulatory institutions be lenient and flexible to allow noncompliant enterprises to smoothly transition to formal economy It is further recommended that more investment in the change management and education of the informal enterprises is made for owners to value formalisation
Keywords: formalisation; enterprises; transition; informal; formal; zambia